2005
DOI: 10.1159/000085771
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and Nandrolone Sensitization of Brain Anteroventral Area of Third Ventricle to Hypertonic NaCl-Induced Sympathetic Response

Abstract: Androgenic steroids increase atherogenesis, thrombogenicity and endothelial dysfunction when administered in high doses, however their effects on NaCl sensitivity of the brain anteroventral area of the third ventricle (ΔV3V) have not been explored. Sprague-Dawley male rats were anesthetized with sodium pentobarbital (40 mg/kg) and the femoral intra-arterial blood pressure and heart rate monitored through a strain-gauge blood pressure transducer and tachograph. ΔV3V microinjections of (2 µl) 1.5 mol/l NaCl solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…The arterial pressure and HR changes observed in testosterone-treated adolescent animals corroborate previous studies demonstrating that, in adulthood, chronic AAS exposure evokes sustained increases in arterial pressure and resting bradycardia [24], [34], [35]. The arterial pressure elevation is very relevant for cardiovascular function once it has been demonstrated that long-term elevations of as little as 5 mmHg in arterial pressure are associated with an increased risk of stroke and coronary heart diseases [36].…”
Section: Discussionsupporting
confidence: 85%
“…The arterial pressure and HR changes observed in testosterone-treated adolescent animals corroborate previous studies demonstrating that, in adulthood, chronic AAS exposure evokes sustained increases in arterial pressure and resting bradycardia [24], [34], [35]. The arterial pressure elevation is very relevant for cardiovascular function once it has been demonstrated that long-term elevations of as little as 5 mmHg in arterial pressure are associated with an increased risk of stroke and coronary heart diseases [36].…”
Section: Discussionsupporting
confidence: 85%
“…Rather than being macrophage-dependent, this change in aortic diameter may be associated with factors, such as blood pressure, which has been shown to be influenced by testosterone [27, 28]. Interestingly, when native males were treated with exogenous testosterone, they had larger body mass and developed AAAs similar to native males (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…14 However, the absence of effects on arterial pressure in animals that received 10-day single administration of testosterone contrasts with previous findings demonstrating that chronic administration of AAS evokes hypertension. 17,27,28 Differences in the treatment time and the AAS used may explain the discrepancy. 17,28 Absence of changes in arterial pressure in cocaine-treated animals corroborates clinical reports that cocaine use is not associated with hypertension in cocaine users.…”
Section: Discussionmentioning
confidence: 99%
“…17,27,28 Differences in the treatment time and the AAS used may explain the discrepancy. 17,28 Absence of changes in arterial pressure in cocaine-treated animals corroborates clinical reports that cocaine use is not associated with hypertension in cocaine users. 29 However, in vitro studies have demonstrated that AAS is capable of potentiating cardiac and vascular effects of cocaine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation